(untitled) (The Review of Diabetic Studies, 2025)
This study aims to assess the level of handling of poisoning and suffocation cases in closed environments within Saudi cities by analyzing the level of preparedness, initial response, quality of medical procedures, and coordination between concerned parties, within the framework of the role of the Saudi Red Crescent Authority in dealing with these emergency cases. The study adopted the descriptive analytical approach to measure employee attitudes and analyze their responses according to three main axes. A questionnaire consisting of 12 items was distributed to a sample of (200) individuals working in the Saudi Red Crescent, and the data were statistically analyzed using arithmetic means, standard deviations, and the (T-test) to measure differences between groups. The reliability coefficient (Cronbach’s alpha) was also calculated to verify the internal consistency validity of the study instrument. The results showed that the average responses of the sample members were high in all three axes, indicating a good level of preparedness, quality of medical procedures, and coordination between health authorities and civil defense when dealing with cases of poisoning and suffocation. The t-test also revealed statistically significant differences attributable to prior training, confirming the importance of training in enhancing field competence. The reliability results showed that the total Cronbach’s alpha value was (0.90), indicating a high reliability of the measurement instrument. The study concludes by emphasizing the importance of strengthening specialized training programs, developing coordination mechanisms between health authorities and field support, in addition to the need to improve the quality of medical procedures provided in closed environments. The study proposes building development programs to raise the level of preparedness and response in emergency situations related to poisoning and suffocation.